Factors of Single Use Plastic Reduction Behavioral Intention - Lee Van; Norhadilah Abdul Hamid; Md. Fauzi Ahmad; Ahmad Nur Aizat Ahmad; Rumaizah Ruslan; Puteri Fadzline Muhamad Tamyez (Emerging Science Journal, 2021)
Malaysia had ranked as eighth over the top 20 countries with mismanaged plastic waste. The largest source of this issue was high consumption of single-use plastic by individuals. It is believed that, residents’ social behaviour played a significant role in reducing single-use plastic, which contributed to decreased plastic pollution. Therefore, this study investigates the factors that affect residents’ single-use plastic behavioural intention in Malaysia using the Theory of Planned Behaviour (TPB). A Quantitative study using survey questionnaire was employed and the total samples were 341 residents in Batu Pahat Johor. All of the data were analysed using regression analysis through Statistical Packages for the Social Sciences (SPSS) software. The results show a positive relationship between all variables except for environmental awareness and law and regulation. At the same time, the most influential factor affecting residents’ single-use plastic reducing behavioural intention was the attitude of residents against lower plastic consumption. Future studies were recommended to be conducted in urban areas which could obtain more desired outcomes. Thus, the findings from this research could provide useful and specific information for policy makers to implement effective strategies for protecting the environmental ecosystem in Malaysia. Doi: 10.28991/esj-2021-01275 Full Text: PDF